Iatrogenic aorta‐coronary dissection: Case report and systematic review. Issue 7 (17th November 2020) - Cereda, Alberto Francesco; Toselli, Marco; Khokhar, Arif; Sticchi, Alessandro; Gallo, Francesco; Ruggiero, Rossella; Ponticelli, Francesco; Laricchia, Alessandra; Mangieri, Antonio; Sangiorgi, Giuseppe; Colombo, Antonio; Giannini, Francesco
Abstract: Objectives and Background: Iatrogenic aorto‐coronary dissection (ICD) is one of the most feared complications of interventional cardiology. Although rare, it is characterized by anterograde coronary ischemia and a concomitant aortic dissection, with potentially fatal consequences. Methods: We present an example case of IACD and an accurate case‐series review of the literature including 125 published cases. Results: There were no significant predisposing factors and the IACD occurred equally in elective and urgent procedures. A significant number of IACDs were associated with CTO procedures. The factors associated with a worse outcome were hemodynamic instability, the presence of anterograde ischemia, and the extent of dissection according to the Dunning classification. Bail‐out stenting was the most used strategy and its failure was associated with mortality. Conclusion: The main features of IACD are anterograde ischemia, retrograde dissection, and hemodynamic instability, each of them should be addressed with no time delay, possibly with bailout stenting, the most employed exit‐strategy. According to our proposed algorithm, a shock team approach is required to coordinate the interdisciplinary skills and enabled patients to receive the best treatment.